Antioxidant Properties of Tonsil-Derived Mesenchymal Stem Cells on Human Vocal Fold Fibroblast Exposed to Oxidative Stress - Sung-Chan Shin; Hyung-Sik Kim; Yoojin Seo; Cho Hee Kim; Ji Min Kim; Hyun-Keun Kwon; Jin-Choon Lee; Eui-Suk Sung; Byung-Joo Lee (Stem Cells International)
The therapeutic potential of tonsil-derived mesenchymal stem cells (TMSCs) has been proved in several in vitro and in vivo models based on their antioxidative capacity. Oxidative stress is involved in the formation of vocal fold scars and the aging of vocal folds. However, few studies have examined the direct correlation between oxidative damage and reconstitution of extracellular matrix (ECM) in the vocal fold fibrosis. We, therefore, sought to investigate the impact of oxidative stress on cell survival and ECM production of human vocal fibroblasts (hVFFs) and the protective effects elicited by TMSCs against oxidative damages in hVFFs. hVFFs were exposed to different concentrations of tert-butyl hydroperoxide in the presence or absence of TMSCs. Cell viability and reactive oxygen species (ROS) production were assessed to examine the progression of oxidative stress in vitro. In addition, expression patterns of ECM-associated factors including various collagens were examined by real-time PCR and immunocytochemical analysis. We found that both cell viability and proliferation capacity of hVFFs were decreased following the exposure to tBHP in a dose-dependent manner. Furthermore, tBHP treatment induced the generation of ROS and reactive aldehydes, while it decreased endogenous activity of antioxidant enzymes in hVFF. Importantly, TMSCs could rescue these oxidative stress-associated damages of hVFFs. TMSCs also downregulated tBHP-mediated production of proinflammatory cytokines in hVFFs. In addition, coculture with TMSC could restore the endogenous matrix metalloproteinase (MMP) activity of hVFFs upon tBHP treatment and, in turn, reduce the oxidative stress-induced ECM accumulation in hVFFs. We have, therefore, shown that the changes in hVFF proliferative capacity and ECM gene expression induced by oxidative stress are consistent with in vivo phenotypes observed in aging vocal folds and vocal fold scarring and that TMSCs may function to reduce oxidative stress in aging vocal folds.